2019
DOI: 10.1002/berj.3555
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion from school in Scotland and across the UK: Contrasts and questions

Abstract: This article draws on findings from the first cross‐national study of school exclusion in the four jurisdictions of the UK. It casts new light on the crucial aspects of children's education that lead to school exclusion. It investigates the reasons for the UK disparities, as well as the policy and practice in place. The focus of this article is on a detailed analysis of the policy context in Scotland, where official permanent exclusion reduced to an all‐time low of just five cases in 2014/15. This is much lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Teachers were reported to be more supportive, with a stronger commitment to children’s rights. A later study by the same author (McCluskey et al ., 2019) showed wide variation between the four UK nations in approaches to school behaviour, exclusion and use of AP, with government guidance in England adopting a much more punitive tone than other countries. Daniels et al ., (2003) found that the majority of their sample of permanently excluded pupils went on to AP, and mostly reported ‘… skilled, understanding teachers working with them in small groups and sometimes one‐to‐one, in ways that contrasted with their experience prior to exclusion’ (p. 92).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers were reported to be more supportive, with a stronger commitment to children’s rights. A later study by the same author (McCluskey et al ., 2019) showed wide variation between the four UK nations in approaches to school behaviour, exclusion and use of AP, with government guidance in England adopting a much more punitive tone than other countries. Daniels et al ., (2003) found that the majority of their sample of permanently excluded pupils went on to AP, and mostly reported ‘… skilled, understanding teachers working with them in small groups and sometimes one‐to‐one, in ways that contrasted with their experience prior to exclusion’ (p. 92).…”
Section: Discussionmentioning
confidence: 99%
“…School exclusion. When discussing disparities in school pupil exclusions, The Report does not mention the recent increase in both temporary and permanent exclusions in England, nor that they have been higher than in Wales, Northern Ireland and Scotland (McCluskey et al, 2019). As The Report acknowledges, exclusion happens especially to children who have special needs, belong to Black-Caribbean communities, are from low-wealth families, are in statutory care or are boys (McCluskey et al, 2019).…”
Section: Education and Trainingmentioning
confidence: 99%
“…When discussing disparities in school pupil exclusions, The Report does not mention the recent increase in both temporary and permanent exclusions in England, nor that they have been higher than in Wales, Northern Ireland and Scotland (McCluskey et al, 2019). As The Report acknowledges, exclusion happens especially to children who have special needs, belong to Black-Caribbean communities, are from low-wealth families, are in statutory care or are boys (McCluskey et al, 2019). However, in focussing on "poor behaviour and inadequate discipline" from the start (p. 76), The Report appears to overlook the way that, as McCluskey et al (2019) highlight, social and emotional difficulties, deprivation and disabilities often underlie poor behaviour when children struggle to communicate.…”
Section: Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own analyses of interview data collected from senior level policymakers and practitioners as part of the Excluded Lives research project: 'Disparities in rates of permanent exclusion from school across the UK' (2017/18), indicated that different policy discourses may help to explain the disparities between the four UK jurisdictions (see: Cole et al 2019, Daniels et al 2019, McCluskey 2019. In the study reported here, we were seeking to explore the findings from the Excluded Lives project further by comparing national school exclusion policy discourses, and their potential effects, in the two UK jurisdictions with the largest disparity in school exclusion rates; England and Scotland.…”
Section: Introductionmentioning
confidence: 99%